PEMANFAATAN MEDIA BARU SEBAGAI MEDIA KOMUNIKASI PEMASARAN GARIS SEPULUH CORPORATION SELAMA MASA PANDEMI COVID-19 (Studi Pada Serial Film Animasi Riko The Series) - Dio Aditya (2022)
Riko The Series is a children's animated film series owned by a company called Garis Sepuluh and was released in February 2020. That time was very close to the arrival of the Covid-19 pandemic in Indonesia, in March 2020. As a start-up company, of course they need a good marketing communication efforts if they want to get new consumers. The pandemic situation created limitations in offline activities so that many activities were shifted to online activities, including marketing communication activities. This study aims to determine the use of new media as a marketing communication medium carried out by Garis Sepuluh during the Covid-19 pandemic and to find out what types of new media are used and which types of new media are efficient and less efficient for marketing communication activities. The research method used is qualitative with a case study approach. Data collection techniques were carried out with in-depth interviews, observation, and documentation activities. From the results of this study, the researchers obtained the results that the new media used by Garis Sepuluh for marketing communication activities for Riko The Series are several types of social media, namely Instagram, Youtube, Twitter, Facebook, TikTok, Whatsapp, Telegram, and also Website. These media are used to carry out many online activities based on the type of marketing communication mix. Garis Sepuluh has used new media for marketing communication activities during the Covid-19 pandemic to increase awareness and get new consumers.